Board Diversity and Corporate Financial Performance：Evidence from China - Feng, Liheng (2022)
Previous analytical literature contains conflicting views regarding the effect of board diversity on corporate performance. Thus, this study aims to examine gender, tenure, age and educational diversity on corporate boards directly correlate with firm financial performance. According to upper echelons theory and agency theory, this study hypothesised that the four above-mentioned attributes of board diversity positively influence corporate financial performance.